Rethinking Resources: The Critical Role of Recycling in the Mining Industry - Yudan Whulanza; Eny Kusrini; Akhmad Herman Yuwono; Sri Harjanto; Nofrijon Sofyan (International Journal of Technology)
In an era of increasing environmental awareness, the mining industry—often criticized for its significant contributions to global greenhouse gas emissions and other ecological impacts—faces growing pressure to innovate and reform (Dunlap and Laratte, 2022). Nonetheless, despite these obstacles exists a promising option that might revolutionize the business and significantly diminish its environmental impact: the recycling and repurposing of essential resources, especially from electronic waste (Primc et al., 2024; Qing et al., 2022). The escalating demand for critical resources such as lithium and cobalt, propelled by the expanding electric vehicle and renewable energy industries, perpetuates environmental and social issues associated with conventional extraction methods (Dunlap, 2023). The industry, responsible for a large portion of global waste, is scrutinized for its practices that endanger both the climate and local communities. Yet, the shift towards a greener mining approach is marred by accusations of greenwashing, with claims of sustainability often falling short of substantial environmental benefits (Zhang et al., 2023; Zharfpeykan, 2021). The Royal Society of Chemistry promotes a shift towards the recovery of valuable metals from electronic trash to address these challenges (Serpe et al., 2025). This initiative represents a dual opportunity: mitigating the growing problem of e-waste— which saw nearly 57 million tonnes discarded in 2021 alone—and providing a source of critical materials without the extensive damage associated with traditional mining methods (Gulliani et al., 2023). Electronic devices like phones, laptops, and tablets contain valuable materials that, if recycled, could significantly lessen the need for fresh mining operations (Liu et al., 2023).The process, however, is not without its challenges. The recovery of materials from e-waste is complex due to their dispersion in small volumes and intricate designs that complicate disassembly. The solution begins with rethinking product design towards easier disassembly and recycling, ensuring that end-of-life products can be efficiently broken down and their materials recovered (Murthy and Ramakrishna, 2022; Zhang et al., 2022). Furthermore, there is a persuasive argument for enterprises to adopt industrial symbiosis—repurposing waste from one sector as raw material for another. This strategy fosters a circular economy and corresponds with rising consumer and regulatory expectations for sustainable behaviors. This transition necessitates strong coordination among companies and may need the redefinition of intellectual property boundaries to enhance recycling and recovery processes.The emphasis on using secondary materials—those recovered from products at the end of their life cycle—offers a path towards a more sustainable mining industry that reduces environmental impact and dependency on raw material extraction (Ramprasad et al., 2022; Kusrini et al., 2020). Mining, extraction, and production of criticial minerals that involving 41 elements such as rare earth elements (REEs), lithium (Li), nickel (Ni) and others are challenging, and need multi-steps processes (Kusrini et al., 2020). One of example process such as adsorption that reported showed environmentally friendly process, higher efficiency, and lower cost (Kusrini et al., 2018). This strategy is not merely about compliance with environmental standards but about reshaping the industry into a more sustainable and responsible entity.